2012
DOI: 10.3402/ijch.v71i0.18580
|View full text |Cite
|
Sign up to set email alerts
|

The health of Inuit children under age 6 in Canada

Abstract: ObjectivesPrevious research has suggested that Inuit children experience poor health as compared to their non-Aboriginal counterparts, although social determinants such as family and social conditions, lifestyle or behaviour, and cultural factors may be at play. The purpose of the current study was to examine the parent-reported health of Inuit children under 6 years of age living in Canada.Study design and methodsData from the 2006 Aboriginal Children's Survey were used to examine measures of Inuit child heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Although it has been documented that postnatal exposures to POPs from breast milk could be a potential health concern for the developing child (Boucher et al, 2012a), many studies have highlighted the very positive effects of breastfeeding which likely outweigh the risks. For example, an assessment from the 2006 Aboriginal Children's Survey has identified breastfeeding as a social determinant of health for Inuit children under age 6 in Canada (Findlay and Janz, 2012). Moreover, Canadian Inuit children who are breastfed may be at lower risk of hospitalization due to respiratory tract infection (Banerji et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Although it has been documented that postnatal exposures to POPs from breast milk could be a potential health concern for the developing child (Boucher et al, 2012a), many studies have highlighted the very positive effects of breastfeeding which likely outweigh the risks. For example, an assessment from the 2006 Aboriginal Children's Survey has identified breastfeeding as a social determinant of health for Inuit children under age 6 in Canada (Findlay and Janz, 2012). Moreover, Canadian Inuit children who are breastfed may be at lower risk of hospitalization due to respiratory tract infection (Banerji et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports based on ACS data have revealed that the rate of reported hunger is 23% among Inuit children, 3% among Métis children, and 5% among off-reserve First Nation children younger than 6 years old [28,29]. This compares to 1% of all children from the NLSCY sample, suggesting that reported hunger is higher among Aboriginal children than Canadian children in general.…”
Section: Prevalence Of Hunger Among Inuit Métis Off-reserve First Nmentioning
confidence: 94%
“…Asthma and allergies are among the most common chronic conditions reported by parents/guardians of indigenous children under the age of 6 years [ 14 , 15 ]. Chang et al found that children and adults with Inuit ancestry, but living outside Nunavut and off the First Nations reserves in other provinces, had a significantly lower prevalence of asthma and allergies compared to children from other indigenous groups [ 16 ].…”
Section: Introductionmentioning
confidence: 99%